2022
DOI: 10.1097/ccm.0000000000005715
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Blood Pressure Threshold During Pediatric Cardiopulmonary Resuscitation and Survival Outcomes: A Multicenter Validation Study*

Abstract: Arterial diastolic blood pressure (DBP) greater than 25 mm Hg in infants and greater than 30 mm Hg in children greater than 1 year old during cardiopulmonary resuscitation (CPR) was associated with survival to hospital discharge in one prospective study. We sought to validate these potential hemodynamic targets in a larger multicenter cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…These intra-arrest diastolic pressure thresholds were selected based on preliminary information generated from a single-center study that showed promising improvement in survival on hospital discharge and in survival with favorable neurologic outcome in 164 participants. Differently, in the current study by Berg et al (1), after adjusting for age, initial rhythm, location (PICU or cardiac ICU [CICU]), and institution, the investigators found an increased rate of survival to hospital discharge and rate of return of circulation, but the risk of survival with favorable neurologic outcome was not different in patients in who the diastolic physiologic endpoints were attained. Disappointed, the investigators speculate that the difference in conclusion between the two studies may be explained by some differences in sample characteristics between the single and multicenter trial and a possible ceiling effect reached in some subgroups.…”
contrasting
confidence: 67%
See 4 more Smart Citations
“…These intra-arrest diastolic pressure thresholds were selected based on preliminary information generated from a single-center study that showed promising improvement in survival on hospital discharge and in survival with favorable neurologic outcome in 164 participants. Differently, in the current study by Berg et al (1), after adjusting for age, initial rhythm, location (PICU or cardiac ICU [CICU]), and institution, the investigators found an increased rate of survival to hospital discharge and rate of return of circulation, but the risk of survival with favorable neurologic outcome was not different in patients in who the diastolic physiologic endpoints were attained. Disappointed, the investigators speculate that the difference in conclusion between the two studies may be explained by some differences in sample characteristics between the single and multicenter trial and a possible ceiling effect reached in some subgroups.…”
contrasting
confidence: 67%
“…In this issue of Critical Care Medicine , in a study authored by Berg et al (1), the investigators tried to answer an important question for clinicians delivering cardiopulmonary resuscitation (CPR) in children: is attaining a diastolic arterial pressure during CPR helpful? They tested the hypothesis that using diastolic pressure-directed intra-arrest resuscitation measures would improve survival.…”
mentioning
confidence: 99%
See 3 more Smart Citations